Youth Organizations in the Soviet Occupation Zone in Germany, 1945–1949 - Elena A. Zharonkina; Vasily S. Krovyakov (СибСкрипт)
The Allied occupation of Germany after World War II remains a popular research topic. In the democratization of German society, the crucial role belonged to youth policy. The article describes youth organizations organized by the Soviet military administration in the Soviet occupation zone of Germany. The authors applied systemic, historical, analytical, and comparative methods to archival documents in order to identify the strategies that the Soviet military administration used to build a system of youth organizations in post-war Germany. Youth work was a challenge for the occupation authorities. On March 7, 1946, the Soviet military administration created the Free German Youth as an anti-fascist organization that united young people from all social strata. The Free German Youth was responsible for the democratic denazification of young Germans and facilitated the economic recovery of the country. It fell under the influence of the Socialist United Party of Germany (1946) and excluded representatives of other parties from its leadership. As a result, the Free German Youth became an agent of the Socialist Unity Party of Germany.